2017
DOI: 10.1002/aenm.201602922
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence of Ion Diffusion for the Silver‐Electrode‐Induced Thermal Degradation of Inverted Perovskite Solar Cells

Abstract: Perovskite solar cells (PSCs) have recently demonstrated high efficiencies of over 22%, but the thermal stability is still a major challenge for commercialization. In this work, the thermal degradation process of the inverted structured PSCs induced by the silver electrode is thoroughly investigated. Elemental depth profiles indicate that iodide and methylammonium ions diffuse through the electron‐trasnporting layer and accumulate at the Ag inner surface. The driving force of forming AgI then facilitates the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
280
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(295 citation statements)
references
References 40 publications
14
280
1
Order By: Relevance
“…Interestingly, the effect is greater in the noncovered regions suggesting that the [60]PCBM layer and/or silver contact slightly protect the device. [33,39,[44][45][46] In both the [60]PCBM and PDI-EH devices, we see the formation of the interfacial AgI layer. The AgI − ion fragment ( Figure S5, Supporting Information) indicates the formation of the interfacial AgI layer, which is fully consistent with the previous findings.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the effect is greater in the noncovered regions suggesting that the [60]PCBM layer and/or silver contact slightly protect the device. [33,39,[44][45][46] In both the [60]PCBM and PDI-EH devices, we see the formation of the interfacial AgI layer. The AgI − ion fragment ( Figure S5, Supporting Information) indicates the formation of the interfacial AgI layer, which is fully consistent with the previous findings.…”
Section: Resultsmentioning
confidence: 99%
“…[125] Consequently, the deteriorated MAPbI 3 thin film, the poor electron extraction, and the generation of AgI barrier resulted in the degradation of PVSCs. The introduction of passivation layer at the perovskite/ETM and ETM/metal electrode interfaces could prohibit ion motion to improve the device stability.…”
Section: Wwwadvenergymatdementioning
confidence: 99%
“…[124] In the work of Wang and co-workers, they clearly demonstrated the reconstruction of grain boundaries caused by ion migration, which may induce defects in both perovskite film and perovskite/PCBM interface. [125] Recently, our group developed a graded 3D-2D perovskite interface with 2D structure passivated grain boundaries. We found that the 2D perovskite could passivate at the surface and grain boundaries of perovskite film which modified the surface energy level and reduced the charge recombination, resulting to an ultrahigh V oc of 1.17 V. And at the same time, the 2D passivated grain boundaries effectively blocked the cross-layer ion diffusion, prevented the migration of I − ion from perovskite layer to PCBM layer, thus dramatically improved the thermal stability of p-i-n PVSC.…”
Section: Wwwadvenergymatdementioning
confidence: 99%
See 1 more Smart Citation
“…The depth profiles of CN − , I − , and Au − of PSCs functioned with the sputtering time from 0 to 600 s are shown in Figure d,e. The CN − ion is attributed to the existence of CH 3 NH 3 + (MA + ) . For the device without FeOOH QDs (Figure d), I − and CN − remarkably diffused into the Au electrode after 360 h at 85 °C, whereas the diffusion of I − and CN − ions is negligible for device with FeOOH QDs (Figure e).…”
Section: Resultsmentioning
confidence: 98%